FEATURES OF THE MODERN CLINICAL COURSE OF CHRONIC HEART FAILURE (Modern American Journal of Medical and Health Sciences, 2025)
Despite significant advances in the treatment of cardiovascular diseases, the prevalence of chronic heart failure (CHF) is not only not declining, but is steadily increasing, with the growth in incidence resembling a non-communicable epidemic. The MONICA study, conducted on a large, unorganized population, showed a CHF prevalence of 2%. A study of city residents over 50 years old, conducted in Rotterdam, established a CHF prevalence of up to 4%. In the Russian population-based EPOCHA-CHF study, the increase in CHF prevalence by clinical criteria was more than 4%, especially in older age groups, reaching 9.7%.